2023
DOI: 10.1186/s12986-022-00719-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel nutrition-related nomogram for the survival prediction of colorectal cancer-results from a multicenter study

Abstract: Background Precisely predicting the short- and long-term survival of patients with cancer is important. The tumor-node-metastasis (TNM) stage can accurately predict the long-term, but not short-term, survival of cancer. Nutritional status can affect the individual status and short-term outcomes of patients with cancer. Our hypothesis was that incorporating TNM stage and nutrition-related factors into one nomogram improves the survival prediction for patients with colorectal cancer (CRC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The higher the stage, the greater the severity of the tumor and the difficulty of treatment. Therefore, TNM staging is applied in many predictive nomograms for colorectal cancer prognosis ( 18 , 19 ). Neural invasion refers to tumor cells invading the nerve sheath or the presence of tumor cells within the nerve sheath, which is associated with tumor invasion, metastasis, cancer-related pain, and poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the stage, the greater the severity of the tumor and the difficulty of treatment. Therefore, TNM staging is applied in many predictive nomograms for colorectal cancer prognosis ( 18 , 19 ). Neural invasion refers to tumor cells invading the nerve sheath or the presence of tumor cells within the nerve sheath, which is associated with tumor invasion, metastasis, cancer-related pain, and poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the incidence of NIS was 89.7%, and the highest proportion of NIS was no appetite (35.3%), followed by dysphagia (29.4%), vomiting (13.2%) and oral pain (12.5%), which is similar to previous studies. 5,30,31 These symptoms can lead to malnutrition and weight loss, with a potential risk of malabsorption. 32 Studies have shown that loss of appetite had a great influence on dietary intake in HNC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CRC patients with the same pathological TNM stage often exhibit signi cantly different prognoses according to various studies (Ng et al, 2019), leading to the inclusion of risk factors such as vascular invasion and extranodal tumor deposits (ENTD) to enhance the predictive power of conventional pathological staging (Ma et al, 2019). This nding suggests that there is room for improvement in the ability of pathological TNM staging to predict CRC patient prognosis (Ruan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%